Kekosongan Hukum Mengenai Penggunaan Ruang Bawah Tanah - Saptomo, Ade; Wilson Salamony, Jetter; Rekayasa Kamal Djunaedi, Tubagus; Reza, Mohammad (JURNAL RETENTUM, 2023)
This study aims to examine the urgency of regulating underground space rights in the Indonesian agrarian legal system, with a focus on the need to provide legal certainty regarding its potential use for various purposes, such as housing, business, and public infrastructure. Using a normative legal method, this study adopts a statute approach to analyze existing legal provisions, such as Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) and other related regulations, as well as a conceptual approach to understand the urgency of regulating underground space in the development of national agrarian law. The research data sources include primary data from relevant laws and regulations, as well as secondary data obtained from legal literature, scientific articles, and in-depth case studies. The results of this study are expected to provide recommendations to fill the legal gap regarding the use of underground space, as well as encourage the creation of legal certainty in the agrarian sector that supports sustainable development and urbanization that is increasingly growing in Indonesia.